ANALYSIS STRATEGY OF BREKSI CLIFF TOURISM DESTINATION DEVELOPMENT IN THE NEW NORMAL PERIOD - Rini Raharti; Bimo Harnaji; Aditya Kurniawan; Dewi Puspitasari (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
Sleman Regency is one of the regencies that is known to have a lot of potential in nature, tourism, and others, one of which is in Prambanan District, namely the Breksi Cliff tourist attraction. This research is descriptive qualitative with the aim of analyzing the strengths, weaknesses, opportunities, and threats of the Breksi Cliff tourism object and formulating a strategy for developing Breksi Cliff tourism objects. Data collection techniques were obtained through observation, interviews, and documentation conducted with the Department of Tourism, Breksi Cliff managers, and visitors. Analysis of the data to determine the strategy of developing a tourist attraction is carried out by a SWOT analysis. Based on the SWOT analysis, the following strategies can be developed: SO (Strength and Opportunities) strategy by 1) Involving the community in all development planning and fostering a sense of community ownership of tourism objects, 2) Increasing promotion through social media. WO (Weaknesses and Opportunities) strategy by 1) Making souvenirs of typical food for Breksi Cliff tourism 2) Increasing the ability of human resources by holding foreign language skills training. ST strategy (Strength and Treats) by 1) Maintaining health protocols for mutual convenience. WT (Weaknesses and Treats) strategy by 1) Maintaining Product and Service Quality to be able to maintain the level of consumer confidence.